2021
DOI: 10.1016/j.bas.2021.100851
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine use by neurosurgeons due to the COVID-19 related lockdown

Abstract: Introduction Due to COVID-19 related restriction, the use of telemedicine has increased tremendously. With this increase, an evaluation in the neurosurgical field seems appropriate. Research question To what extent has telemedicine made its way in neurosurgical practice during the COVID-19 pandemic? Material and Methods A 29-question survey was distributed among members of the congress of neurological surgeons regarding (Barsom et al., 2020) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Literature presents contrasting data in this respect. A survey among members of the Congress of Neurological Surgeons [ 25 ], to which 363 members responded, indicated that on average 60% of consultations had been converted to telehealth consults. 70% of responders expected telemedicine to increase urgent appointments but 56% thought that it could decrease the quality of the relationship between practitioners and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literature presents contrasting data in this respect. A survey among members of the Congress of Neurological Surgeons [ 25 ], to which 363 members responded, indicated that on average 60% of consultations had been converted to telehealth consults. 70% of responders expected telemedicine to increase urgent appointments but 56% thought that it could decrease the quality of the relationship between practitioners and patients.…”
Section: Discussionmentioning
confidence: 99%